Correlating in silico elucidation of interactions between hydroxybenzoic acids and casein with in vitro release kinetics for designing food packaging. (June 2022) - Khan, Muhammad Rehan; Volpe, Stefania; Sadiq, Muhammad Bilal; Giannino, Francesco; Torrieri, Elena
Abstract: The sustained release of phenolic compounds from packaging films is of prime importance for extending the shelf-life of food products. Thus, understanding the interaction of phenolic compounds with polymeric chains and their influence on release kinetics is of great value since release behavior has a role in controlling the quality of the food product. In this study, the interaction mechanism of a group of hydroxybenzoic acids (gallic, vanillic, and protocatechuic acid) with casein fractions was studied by using molecular docking methods. Sodium caseinate film was developed through the solution casting method. Furthermore, the release kinetics of gallic acid was elucidated into the food simulant (95% ethanol). The interaction of phenolic acids with casein fractions was a spontaneous reaction mainly driven by hydrogen bonding, Van der Waals, and hydrophobic forces. The IC50 of gallic acid in terms of DPPH radical scavenging activity was observed to be 30.67 µg/ml, whereas the maximum radical scavenging activity was observed to be ~57%. Furthermore, approximately 26% of the gallic acid was released from the packaging into the simulant. A mathematical model was used to describe the diffusion of gallic acid from the packaging material, which will provide essential information on developing packaging materials based on sodium caseinate to reach the best engineering solution by keeping in view the regulatory constraints on the leeching phenomenon. Finally, the developed film can only be used for packaging purposes of food products with lipophilic surface properties. Highlights: Molecular docking methods were used for studying interaction mechanism. ~26% of the gallic acid was released from the packaging into the simulant The IC50 of gallic acid was observed to be 30.67 µg/ml. Fick's second law was numerically solved based on finite differences methodology. The diffusion coefficient was 5.99 × 10–12 m2/s.